sami2py—Overview and applications - Klenzing, Jeff; Smith, Jonathon M.; Halford, Alexa J.; Huba, J. D.; Burrell, Angeline G. (Frontiers in Astronomy and Space Sciences, 2022)
sami2py is a Python module that runs the SAMI2 (Sami2 is Another Model of the Ionosphere) ionospheric model, as well as load and archive the results. SAMI2 is a model developed by the Naval Research Laboratory to simulate the motions of plasma in a two-dimensional ionospheric environment along a dipole magnetic field. SAMI2 solves for the chemical and dynamical evolution of seven ion species in this environment (H+, He+, N+, O+, N+2 , NO+, and O+2 ). The Python implementation allows for additional modifications to the empirical models within SAMI2, including the exospheric temperature in the empirical thermosphere and the input of E×B ion drifts. The code is open source and available to the community on GitHub. The work here discusses the implementation and use of sami2py, including integration with the pysat ecosystem and the growin python package for ionospheric calculations. As part of the Application Usability Level (AUL) framework, we will discuss the usability of this code in terms of several ionospheric applications.